Cardiovascular risk reduction in hypertension: angiotensin‐converting enzyme inhibitors, angiotensin receptor blockers. Where are we up to?. Issue 3 (March 2016) - Sindone, A.; Erlich, J.; Lee, C.; Newman, H.; Suranyi, M.; Roger, S. D.
Abstract : Previously, management of hypertension has concentrated on lowering elevated blood pressure. However, the target has shifted to reducing absolute cardiovascular (CV) risk. It is estimated that two in three Australian adults have three or more CV risk factors at the same time. Moderate reductions in several risk factors can, therefore, be more effective than major reductions in one. When managing hypertension, therapy should be focused on medications with the strongest evidence for CV event reduction, substituting alternatives only when a primary choice is not appropriate. Hypertension management guidelines categorise angiotensin‐converting enzyme inhibitors (ACEI) and angiotensin receptor blockers (ARB) interchangeably as first‐line treatments in uncomplicated hypertension. These medications have different mechanisms of action and quite different evidence bases. They are not interchangeable and their prescription should be based on clinical evidence. Despite this, currently ARB prescriptions are increasing at a higher rate than those for ACEI and other antihypertensive classes. Evidence that ACEI therapy prevents CV events and death, in patients with coronary artery disease or multiple CV risk factors, emerged from the European trial on reduction of cardiac events with perindopril in stable coronary artery disease (EUROPA) and Heart Outcomes Prevention Evaluation (HOPE) trials respectively. The consistent benefit has been demonstrated in meta‐analyses. The clinical trial data for ARB are less consistent, particularly regarding CV outcomes and mortality benefit. The evidence supports the use of ACEI (Class 1a) compared with ARB despite current prescribing trends.